Being Flexible: The Voltage-Controllable Activation Gate of Kv Channels - Labro, Alain J.; Snyders, Dirk J. (Frontiers in Pharmacology, 2012)
Kv channels form voltage-dependent potassium selective pores in the outer cell membrane and are composed out of four α-subunits, each having six membrane-spanning α-helices (S1–S6). The α-subunits tetramerize such that the S5–S6 pore domains co-assemble into a centrally located K+ pore which is surrounded by four operational voltage-sensing domains (VSD) that are each formed by the S1–S4 segments. Consequently, each subunit is capable of responding to changes in membrane potential and dictates whether the pore should be conductive or not. K+ permeation through the pore can be sealed off by two separate gates in series: (a) at the inner S6 bundle crossing (BC gate) and (b) at the level of the selectivity filter (SF gate) located at the extracellular entrance of the pore. Within the last years a general consensus emerged that a direct communication between the S4S5-linker and the bottom part of S6 (S6c) constitutes the coupling with the VSD thus making the BC gate the main voltage-controllable activation gate. While the BC gate listens to the VSD, the SF changes its conformation depending on the status of the BC gate. Through the eyes of an entering K+ ion, the operation of the BC gate apparatus can be compared with the iris-like motion of the diaphragm from a camera whereby its diameter widens. Two main gating motions have been proposed to create this BC gate widening: (1) tilting of the helix whereby the S6 converts from a straight α-helix to a tilted one or (2) swiveling of the S6c whereby the S6 remains bent. Such motions require a flexible hinge that decouples the pre- and post-hinge segment. Roughly at the middle of the S6 there exists a highly conserved glycine residue and a tandem proline motif that seem to fulfill the role of a gating hinge which allows for tilting/swiveling/rotations of the post-hinge S6 segment. In this review we delineate our current view on the operation of the BC gate for controlling K+ permeation in Kv channels.